1986
DOI: 10.1200/jco.1986.4.12.1827
|View full text |Cite
|
Sign up to set email alerts
|

Use of in vitro dose response effects to select antineoplastics for high-dose or regional administration regimens.

Abstract: Several preclinical and clinical studies have documented that dose or dose intensity of chemotherapeutic agents are important factors for response of patients' tumors. This finding has prompted empiric trials of certain chemotherapeutic agents in high-dose or regional administration treatment regimens. The present study was performed to identify agents that would be particularly good candidates for high-dose or regional administration regimens against particular types of tumors. Using a human tumor cloning tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In the case of cisplatin, there is evidence to suggest that this in vivo resistance can develop rapidly with as few as 1 or 2 exposures to the drug 3 . Using in vitro models, there is also evidence that for most tumors acquired cisplatin resistance is mild to moderate and can be overcome with drug concentrations 5 to 10 times greater than the therapeutic equivalent 1,4,5 . Teicher, et al 1 demonstrated a linear dose‐response relationship for a head and neck carcinoma cell line, which indicated that an additional cell kill of 10 × 2 logarithmic power occurred as a result of doubling the cisplatin dose 1 …”
Section: Introductionmentioning
confidence: 99%
“…In the case of cisplatin, there is evidence to suggest that this in vivo resistance can develop rapidly with as few as 1 or 2 exposures to the drug 3 . Using in vitro models, there is also evidence that for most tumors acquired cisplatin resistance is mild to moderate and can be overcome with drug concentrations 5 to 10 times greater than the therapeutic equivalent 1,4,5 . Teicher, et al 1 demonstrated a linear dose‐response relationship for a head and neck carcinoma cell line, which indicated that an additional cell kill of 10 × 2 logarithmic power occurred as a result of doubling the cisplatin dose 1 …”
Section: Introductionmentioning
confidence: 99%
“…Although the introduction of cisplatin and the use of combination chemotherapy has improved response rates and survival compared with therapy using alkylating agents, this improvement had been modest 2. Retrospective analysis of published trials as well as in vitro studies had suggested that objective tumor response rates are increased with regimens that deliver greater platinum dose intensity 3, 4. However, the results of randomized trials addressing this question are controversial, with no clear evidence of superior results with the dose‐intense regimens and an increase in treatment‐related toxicity 5‐10…”
mentioning
confidence: 99%
“…7,8 According to in vitro studies, a minimum four-fold increase in dose intensity is necessary to overcome resistance to chemotherapy. [9][10][11] Single high-dose chemotherapy followed by stem cell rescue results in a four-fold or higher dose intensity compared to standard chemotherapy. This therapy yields remission rates between 50% and 80%, even in relapsed patients.…”
mentioning
confidence: 99%